Could electrical conductivity replace water level in rating curves for alpine streams?. Issue 1 (25th January 2013) - Weijs, Steven V.; Mutzner, Raphaël; Parlange, Marc B.
Key Points: Explicitly look at uncertainty in streamflow rating curve Strong predictive power of electrical conductivity Reduces uncertainty in streamflow by 44% Abstract : [1] Streamflow time series are important for inference and understanding of the hydrological processes in alpine watersheds. Because streamflow is expensive to continuously measure directly, it is usually derived from measured water levels, using a rating curve modeling the stage‐discharge relationship. In alpine streams, this practice is complicated by the fact that the streambed constantly changes due to erosion and sedimentation by the turbulent mountain streams. This makes the stage‐discharge relationship dynamic, requiring frequent discharge gaugings to have reliable streamflow estimates. During an ongoing field study in the Val Ferret watershed in the Swiss Alps, 93 streamflow values were measured in the period 2009–2011 using salt dilution gauging with the gulp injection method. The natural background electrical conductivity in the stream, which was measured as by‐product of these gaugings, was shown to be a strong predictor for the streamflow, even marginally outperforming water level. Analysis of the residuals of both predictive relations revealed errors in the gauged streamflows. These could be corrected by filtering disinformation from erroneous calibration coefficients. In total, extracting information from the auxiliary data enabled to reduce the uncertainty in the rating curve, as measured by the root‐mean‐square error in log‐transformed streamflow relative to that of the original stage‐discharge relationship, by 43.7%.